Crystal Growth of Materials with the ThCr2Si2 Structure Type. Issue 2 (15th October 2019) - Kliemt, Kristin; Peters, Marius; Feldmann, Fabian; Kraiker, Alexej; Tran, Doan‐My; Rongstock, Susanna; Hellwig, Johannes; Witt, Sebastian; Bolte, Michael; Krellner, Cornelius
Abstract: The single crystal growth of 19 different intermetallic compounds within the LnT2 X2 family (with Ln = lanthanides, T = Co, Ru, Rh, Ir, and X = Si, P) is presented, by employing a high‐temperature metal‐flux technique. The habitus of the obtained crystals is platelet‐like with the crystallographic c direction perpendicular to the surface and with individual masses between 1 and 100 mg. The magnetic properties of these crystals are characterized by magnetization, heat‐capacity, and resistivity measurements. These crystals form the materials basis for a thorough study of exciting surface properties by angle‐resolved photoemission spectroscopy. Abstract : Single crystal of CeRu2 P2 is shown in the image together with the ThCr2 Si2 structure type. In this work, the single crystal growth of 19 different intermetallic compounds within this structure type is presented using a high‐temperature metal‐flux technique.